2020
DOI: 10.1002/ncp.10570
|View full text |Cite
|
Sign up to set email alerts
|

Review of Preterm Human‐Milk Nutrient Composition

Abstract: Background The human milk–fed preterm infant is at risk for growth failure, micronutrient deficiencies, and neurocognitive delay. Although protective and better tolerated than formula, human milk alone cannot meet the high nutrient requirements of this population, and fortification is necessary. Clinicians use assumptions of preterm human‐milk composition to determine the type and quantity of fortification. Objectives The objectives of this review were to identify evidence of macronutrient and micronutrient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…The overall fluid intake (EN + PN) was started with 70–90 ml/kg/day and was increased by 10–20 ml/kg/day until the achievement of 150–180 ml/ kg/day, which was aimed to be reached by 7 to 10 DOL 30 . Preterm HM was assumed to contain 65 kcal/100 ml (1.5 g of protein/100 ml, 3.5 g of fat/100 ml, 6.9 g of carbohydrate/100 ml) 31 . Macronutrients’ content of formula (Pre-Nidina Nestlè, Milan, Italy) and of PN were calculated based on the published manufacturer’s labels, including proteins (TrophAmine 6% Braun Medical Inc. Irvine, USA), lipids (Smoflipd, Fresenius Kabi, USA), and carbohydrates (Dextrose injection 10%, Fresenius Kabi, USA) expressed in g/kg/day 32 .…”
Section: Methodsmentioning
confidence: 99%
“…The overall fluid intake (EN + PN) was started with 70–90 ml/kg/day and was increased by 10–20 ml/kg/day until the achievement of 150–180 ml/ kg/day, which was aimed to be reached by 7 to 10 DOL 30 . Preterm HM was assumed to contain 65 kcal/100 ml (1.5 g of protein/100 ml, 3.5 g of fat/100 ml, 6.9 g of carbohydrate/100 ml) 31 . Macronutrients’ content of formula (Pre-Nidina Nestlè, Milan, Italy) and of PN were calculated based on the published manufacturer’s labels, including proteins (TrophAmine 6% Braun Medical Inc. Irvine, USA), lipids (Smoflipd, Fresenius Kabi, USA), and carbohydrates (Dextrose injection 10%, Fresenius Kabi, USA) expressed in g/kg/day 32 .…”
Section: Methodsmentioning
confidence: 99%
“…The human milk composition of mothers who gave birth to preterm infants differed from that of mothers who delivered term infants [25]. Early preterm milk was found to be naturally enriched for protein, with several studies suggesting that protein content may be as high as 4.1 AE 2.1 g/100 ml [26]. Sahin et al [27] found protein levels varied between 1.2-2.1 g/100 ml in preterm milk and 1.0-2.6 g/ 100 ml in term milk.…”
Section: Key Pointsmentioning
confidence: 99%
“…Preterm formula (Pre-Nidina Nestlè, Milan, Italy) was administered when human milk was not available or sufficient. Preterm human milk was assumed to contain 65 Kcal/100 mL (1.5 g of protein/100 mL, 3.5 g of fat/100 mL, 6.9 g of carbohydrate/100 mL) [25].…”
Section: Nutritional Protocolmentioning
confidence: 99%